Penggunaan Media Audio Visual untuk Meningkatkan Kemampuan Menulis Fabel di Kelas VII SMP Negeri 2 Sabbangparu - Umar, Ratnawati; Ebe, Andi; Anies, Hasriyati; Wandira, Rizki (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2023)
The aim of this research is to determine and describe the ability to write fables through audio-visual media of class VII students at SMP Negeri 2 Sabbangparu. Data collection techniques through observation, tests and documentation. The results of the research showed that in cycle I, 8 out of 18 students or around 44.44% had the ability to write fables using audio-visual media in class VII.1 of SMP Negeri 2 Sabbangparu, in terms of the overall ability of students in class VII.1 of SMP Negeri 2 Sabbangparu. has not met the minimum completion criteria (KKM) standards that have been determined, namely 70 and is still below 75%. In cycle II, it showed that 14 out of 18 students or around 77.77% of students were able to write fables using audio visual media in class VII.1 of SMP Negeri 2 Sabbangparu. Overall, it has met the specified Minimum Completeness Criteria (KKM) standards, namely 70 and exceeds 75%. This shows a significant increase from cycle I to cycle II.